An integrated approach for progress tracking in liquefied natural gas construction - Wang, J.; Shou, Wenchi; Wang, Xiangyu; Chi, Hung-Lin (2015)
© Springer International Publishing Switzerland 2015.Progress tracking is an essential management function for successful delivery of Liquefied Natural Gas (LNG) projects. It relies on accurate and prompt data collection from construction sites and project participants, which is then used to early detect actual or potential schedule delay. Currently, many Information Technology (IT)-supported methods have been implemented to improve progress tracking. However, none of them has been able to deliver satisfactory and reliable information. This paper aims to develop an integrated approach for construction progress tracking by integrating laser scanning, Building Information Modeling, mobile computing and Radio Frequency Identification. The approach consists of three modules: milestone progress tracking, onsite activity/Task progress tracking, and supply chain tracking. Finally, a pilot LNG project was selected to validate this approach.